2015
DOI: 10.1016/j.fsi.2015.02.040
|View full text |Cite
|
Sign up to set email alerts
|

The new insights into the oyster antimicrobial defense: Cellular, molecular and genetic view

Abstract: Oysters are sessile filter feeders that live in close association with abundant and diverse communities of microorganisms that form the oyster microbiota. In such an association, cellular and molecular mechanisms have evolved to maintain oyster homeostasis upon stressful conditions including infection and changing environments. We give here cellular and molecular insights into the Crassostrea gigas antimicrobial defense system with focus on antimicrobial peptides and proteins (AMPs). This review highlights the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 131 publications
(234 reference statements)
1
67
0
1
Order By: Relevance
“…PST-induced programmed cell death may have important consequences on oyster defense from pathogens, as hemocytes play a key role in oyster immune response. These cell types are involved in a series of cellular immune reactions, such as phagocytosis of invading microorganisms, formation of nodules and capsules surrounding pathogens and their subsequent degradation through the release of host defense molecules (Bachere et al 2015). Hemocytes are able to migrate from the hemolymph to connective tissues and promote localized responses following injury or microorganism invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PST-induced programmed cell death may have important consequences on oyster defense from pathogens, as hemocytes play a key role in oyster immune response. These cell types are involved in a series of cellular immune reactions, such as phagocytosis of invading microorganisms, formation of nodules and capsules surrounding pathogens and their subsequent degradation through the release of host defense molecules (Bachere et al 2015). Hemocytes are able to migrate from the hemolymph to connective tissues and promote localized responses following injury or microorganism invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, hemocytes freshly withdrawn from oyster adductor muscle were plated at a cell density sorted by size and granularity (blue) as described previously (Bachere et al 2015) and the percentage of TMRNEL-labeled cells (red) per population was determined using a BD LSR Fortessa™ flow cytometer analyzer.…”
Section: Membrane Permeabilization By Cytox Green Assaymentioning
confidence: 99%
“…Some families appear to have evolved within specific phyla or species [31], whereas others are found in a diversity of phyla [32]. Most AMP families from molluscs, including defensins, big defensins and BPI (for recent review, see [33]), are also found in other protostomes (Ecdysozoa) and/ or in deuterostomes (Mammalia). By contrast, in cnidarians, taxonomically restricted AMPs have been described, such as arminins, which are among the most highly expressed genes in Hydra [34], or damicornin in the coral Pocillopora damicornis [43].…”
Section: Antimicrobial Peptides In Marine Invertebratementioning
confidence: 99%
“…A large number of immune effectors have been identified in molluscs including diverse antimicrobial peptides or proteins (AMPs), lysozymes, proteases, ribonucleases and oxidases [6,[129][130][131]. Diverse cysteine-rich AMPs have been reported in mussels including defensins, big defensins, mytilins, myticins, mytimacins, mytimycins, myticusins and mytiCRPs [129].…”
Section: (H) Immune Effectorsmentioning
confidence: 99%